Ensino de ciências e divulgação científica: análise das recontextualizações entre as revistas CartaCapital e Carta na Escola - Pezzo, Mariana Rodrigues (Universidade Federal de São Carlos, 2011)
The interfaces between the fields of Education and Communication are gaining prominence and relevance in recent years, either in everyday practices related to professional performance in both areas or in academic literature. This work is inserted in the effort to understand these interfaces, focusing on the practice of scientific communication, analyzed on the basis of theoretical inputs from the area of Science Education especially those identified with the approaches based on the interrelationships between Science, Technology and Society and understood as a space of complementarity between formal and nonformal education. To achieve its goals, the research analyzes the process of recontextualization and interpretation between the reports published in a weekly magazine of updates named CartaCapital and the resulting texts published in Carta na Escola, a monthly magazine that, from these reports, intends to offer high school teachers subsidies to approach the updates in the classroom. The purpose of this analysis conducted from the perspective of discursive textual analysis was, in general, to enrich the understanding of possible and productive relationships between the fields of Media and Education. In addition, we sought to contribute specifically to the understanding of the limits and potencial of using scientific communication products in science teaching and of the roles that the use of media materials aimed at carrying information on science and technology can play in overcoming challenges related to science teaching approaches guided by the interrelationships between Science, Technology, Society and Environment. The results of this analysis showed the dominant presence of recontextualization processes that aim to offer, within Carta na Escola, coordinated, contextualized and historical approaches to updates reported in CartaCapital in a fragmentary way, using a variety of strategies related to the different roles assigned to updates within the teaching proposals presented for the different knowledge areas in Carta na Escola. Specifically in relation to texts identified with the curriculum area of Natural Sciences, Mathematics and its technologies, the research showed different combinations, in Carta na Escola, of scientific, technological and social dimensions concerning the production of science and technology and also of internalist and externalist approaches of science, indicating the potential use of analysis of these dimensions and approaches in the evaluation and critical reading of science dissemination texts.
Keywords: Educação; Mídia impressa; Abordagem CTS; Cultura científica; Jornalismo; Education; Communication; Science teaching; Science dissemination; Print media; STS education; CIENCIAS HUMANAS::EDUCACAO